Gap Assessment of CSA-CIS Stakeholder in Ghana - Damba, Osman Tahidu; Ayambila, Sylvester; Alhassan, Abdallah (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Climate change effects requires a multidimensional and multisectoral approach towards minimizing it effects on farm productivity. This therefore calls for a identifying needs and gaps in building farmers and other value chain actors capacity towards combacting climate change effects. Although attempts through programmes and projects have been made over the last decade, the need for a geographical based and sustainable climate smart agricultural practice promotion is required to ehance adaptation and productivity. This therefore calls for a detailed assessment of the approaches and strategies employed by stakeholders towards best practices. This assessments identified tailor made capacity building and the provision of real time but simple climate information services for effective uptake and utilization.